Ecological trays based on banana (Musa paradisiaca) and achira (Canna indica) leaf blades: Physical, mechanical and chemical characteristics (Agroindustrial Science, 2021)
The accumulation of plastics in our environment has generated serious eco-environmental problems and the need to look for alternatives for the production of bioplastic. The purpose of this work was to evaluate the effect of the proportion of fibers from vegetable leaves (banana and achira) with oca starch on the physical and mechanical properties of biodegradable trays made through the thermoforming process. 3 percentages (2.5%, 5% and 7.5%) of natural fiber with a size between 53 - 75 µm were used. The formulated trays were evaluated by their physical properties (color, thickness, density, humidity and water absorption), mechanical (resistance to tension, elongation and perforation) and Fourier transform infrared spectroscopy (FT-IR).). The results showed trays with adequate expansion, homogeneously distributed fibers and acceptable appearance. As the fiber concentration increased, the ability to absorb water increased, however, the moisture content, puncture resistance and fracturing decreased. In general, the tray with 2.5% banana leaf fiber obtained the best results. These trays can be used to pack dry food with a short shelf life and can be a viable alternative to replace polystyrene trays.